Synthesis and Properties of Modified Polycarbonates by Organosilazasiloxanes - Lekishvili, Nodar; Kotrelev, Gennady (Asian Journal of Chemistry, 2010)
Modification of the polycarbonate based on "bisphenol A" by organosilazasiloxanes has been carried out. Modification obtained via interaction of the silazasiloxy-fragments into the polycarbonate main chain and by addition of small amounts of polyorgano-silazasiloxyarylenes. The composition and structure of the polysilazasiolxanecarbonates have been studied. The properties of modified polycarbonates have been investigated.